2008
DOI: 10.1177/1077801208315525
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Among Pregnant Thai Women

Abstract: The purposes of this study are to describe intimate partner violence (IPV) among pregnant women in Thailand and compare maternal characteristics, health practices during pregnancy, and maternal health between abused and nonabused pregnant women. Of 475 pregnant Thai women, 13.1% report ever being abused, whereas 4.8% report physical abuse during pregnancy. Women abused during pregnancy, compared to nonabused women, are more likely to be younger, unmarried, have low income, be unemployed, and report that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 56 publications
6
35
1
1
Order By: Relevance
“…This result is consistent with another study [29]. This may be due to the lower socioeconomic problem and lack of information on the advantage of on-time ANC initiation.…”
Section: Discussionsupporting
confidence: 83%
“…This result is consistent with another study [29]. This may be due to the lower socioeconomic problem and lack of information on the advantage of on-time ANC initiation.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the current study corroborate those of other research carried out in developed countries, [25][26][27] in which pregnant women who were victims of intimate violence during gestation presented higher chance of having inadequate prenatal care according to the patterns established by the institutions linked with women's and children's health. Having been victim of at least one act of physical violence committed by the partner during gestation more than doubles the chance of having a low quality prenatal care.…”
Section: Discussionsupporting
confidence: 82%
“…The association between depressive symptoms and IPV was particularly strong when abuse occurred both before and during pregnancy and consisted of both physical or sexual abuse (Dolatian et al 2010;Gao et al 2010;Leung et al 2002;Ludermir et al 2010;Martin et al 2006;Patel et al 2002;Savarimuthu et al 2010;Thananowan and Heidrich 2008;Urquia et al 2011;Valentine et al 2011;Varma et al 2007). However, one article found that violence during pregnancy was a contributor of general anxiety but not depressive symptoms (Nasreen et al 2011).…”
Section: Relationship Between Ipv and Perinatal Depressionmentioning
confidence: 97%